2019
DOI: 10.1155/2019/7945983
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Reductase-1 Inhibition Augments Endogenous Glutathione-Dependent Antioxidant Responses in Experimental Bronchopulmonary Dysplasia

Abstract: Background Aurothioglucose- (ATG-) mediated inhibition of thioredoxin reductase-1 (TXNRD1) improves alveolarization in experimental murine bronchopulmonary dysplasia (BPD). Glutathione (GSH) mediates susceptibility to neonatal and adult oxidative lung injury. We have previously shown that ATG attenuates hyperoxic lung injury and enhances glutathione- (GSH-) dependent antioxidant defenses in adult mice. Hypothesis The present studies evaluated the effects of TXNRD1 inhibition on GSH-dependent antioxidant defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…For a comprehensive review, the reader is directed to a recent publication by Saha and colleagues, which extensively summarizes key relationships between NRF2/ARE, inflammatory mediator expression, canonical and non-canonical NFκB pathway activation, and macrophage metabolism [ 18 ]. We have extensively studied the effects of AFN and ATG in the setting of hyperoxia exposure and have consistently observed decreases in inflammation, tissue injury, and cell death [ 2 , 5 , 6 , 19 , 20 , 21 ]. Despite our robust experimental evidence of decreased inflammation in lung injury models, the mechanisms by which gold compounds attenuate pro-inflammatory responses have not been revealed in our studies of lung epithelia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a comprehensive review, the reader is directed to a recent publication by Saha and colleagues, which extensively summarizes key relationships between NRF2/ARE, inflammatory mediator expression, canonical and non-canonical NFκB pathway activation, and macrophage metabolism [ 18 ]. We have extensively studied the effects of AFN and ATG in the setting of hyperoxia exposure and have consistently observed decreases in inflammation, tissue injury, and cell death [ 2 , 5 , 6 , 19 , 20 , 21 ]. Despite our robust experimental evidence of decreased inflammation in lung injury models, the mechanisms by which gold compounds attenuate pro-inflammatory responses have not been revealed in our studies of lung epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…FDA-approved pharmaceutical gold compounds, such as aurothioglucose (ATG) and auranofin (AFN), decrease inflammation in the context of hyperoxic exposure and many other inflammatory diseases [ 3 ]. We and others have described a reduction in inflammatory cell numbers and cytokine expression in the lung following treatment with ATG or AFN [ 4 , 5 , 6 , 7 ]. Isakov et al reported that macrophages treated with AFN and subsequently induced by lipopolysaccharide (LPS) demonstrated selective repression of inflammatory genes such as interleukin (IL)-1 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auranofin can also inhibit phagocytosis by macrophages and can reduce proinflammatory cytokines through the inhibition of nuclear factor-kappa B activation [ 29 , 30 , 31 ]. In addition, auranofin has the antioxidant property of enhancing the activation of nuclear factor erythroid-2-related factor 2 [ 32 , 33 , 34 ]. However, to date, no research has been done on whether auranofin can improve NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…GPx and thioredoxin reductase, two selenoproteins, are important members of the body's antioxidant system ( 46 ). GPx-1 activity decreases dramatically in Se deficiency and increases during Se supplementation.…”
Section: Se Deficiencymentioning
confidence: 99%